(3NQjOI GdbUQ hLQjOI Cgd GdYUQs - (3eMeO Hf eMeO MGeO GdCUHgGfj, YeGO GdOjf GdcGJH,J (B597 (3g` s
(3ChdgG (B:s
(3bGajI GdYjf s
(3BNQgG (B:s
(3BNQ GdbSe GdKGfi ef cJGH NQjOI GdbUQ hLQjOI GdYUQ s
(3ZjQ ebQhAI HTcd hGVM fgGFjkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B26s
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(273) s
Keywords: (3GdCOHs